2005
DOI: 10.2135/cropsci2004.0323
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Performance of Rht Alleles in a Spring Wheat Population across a Range of Moisture Levels

Abstract: The Rht-B1b and Rht-D1b alleles, which occur at homoeologous loci on chromosomes 4B and 4D, respec-Reduced height alleles at the Rht-B1 and Rht-D1 loci have been tively, reduce sensitivity to gibberellic acid (GA), which widely incorporated into wheat (Triticum aestivum L.) cultivars with the intent of improving partitioning of assimilates to grain. Although is necessary for stem elongation (Flintham et al., 1997). generally effective at increasing yield in high yield environments, In favorable environments, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
82
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 29 publications
10
82
3
1
Order By: Relevance
“…However, the Rht-ba genotype was taller than the Rht-ab in Australia, Germany, China and the UK (Fischer and Quail 1990;Börner et al 1993;Tang et al 2009;Kumar et al 2011), suggesting that these genotypes might not be identical for growth and/or development. Although not statistically significant, the Rht-ba genotype was also taller than Rht-ab in the four environments used by Butler et al (2005) in the USA. In a limited number of irrigated experiments in southern New South Wales, Fischer and Quail (1990) suggested that the Rht-ab genotype might have a yield advantage over the Rht-ba genotype at lower yield levels.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, the Rht-ba genotype was taller than the Rht-ab in Australia, Germany, China and the UK (Fischer and Quail 1990;Börner et al 1993;Tang et al 2009;Kumar et al 2011), suggesting that these genotypes might not be identical for growth and/or development. Although not statistically significant, the Rht-ba genotype was also taller than Rht-ab in the four environments used by Butler et al (2005) in the USA. In a limited number of irrigated experiments in southern New South Wales, Fischer and Quail (1990) suggested that the Rht-ab genotype might have a yield advantage over the Rht-ba genotype at lower yield levels.…”
Section: Introductionmentioning
confidence: 64%
“…The Rht genes code for DELLA proteins, which are transcription factors that affect plant growth and stress tolerance (Wilhelm et al 2013). In southern Australia, the difference between the Rht-ba and Rht-ab semi-dwarf genotypes with respect to heading date is negligible (Fischer and Quail 1990;Cane et al 2013), which was also the case in Germany and the USA (Börner et al 1993;Butler et al 2005). However, the Rht-ba genotype was taller than the Rht-ab in Australia, Germany, China and the UK (Fischer and Quail 1990;Börner et al 1993;Tang et al 2009;Kumar et al 2011), suggesting that these genotypes might not be identical for growth and/or development.…”
Section: Introductionmentioning
confidence: 99%
“…However, reduced kernel size and/or low test weight has been a problem in semidwarf compared with conventional (tall) height genotypes. This has been documented in both durum wheat (Joppa 1973;Gale et al 1981;McClung et al 1986) and common wheat (McNeal et al 1972;Knott 1986;Nizam Uddin and Marshall 1989;Butler et al 2005), although, a cross studied by Busch and Chamberlain (1981) did not follow this pattern. Lebsock and Amaya (1969) also found a positive correlation between kernel size and plant height in lines derived from crosses involving non-dwarf durum genotypes of varying height.…”
mentioning
confidence: 92%
“…Lebsock and Amaya (1969) also found a positive correlation between kernel size and plant height in lines derived from crosses involving non-dwarf durum genotypes of varying height. Gale et al (1981) speculated that reduced kernel size may be a primary effect of the Rht genes and, similarly, Butler et al (2005) suggested pleiotropy as the cause.…”
mentioning
confidence: 99%
“…Rht-B1b and Rht-D1b, located on homoeologous chromosome arms of 4BS and 4DS, had pleiotropic effects on plant growth, causing reductions in coleoptile length and seedling leaf area [7]. The effect of the Rht-B1 and Rht-D1 on height reduction is commonly reported at around 20-25% of the wild-type allele but it varies with different genetic background and environment [8][9][10]. Apart from reducing the plant height of wheat, dwarfing genes Rht-B1b, Rht-D1b also decrease the coleoptiles length, the seedling rate and population density [11,12].…”
Section: Introductionmentioning
confidence: 99%